The relationship between the speed of early initiation of breastfeeding mothers with post partum pain scale on stage four - YUNARSIH - (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2015)
The earlyinitiation of breastfeeding mothers after the delivery happens is possible believed that can decrease the pain of delivery because it is one of distraction acts which can change the mother’s focus on the pain of delivery into another stimulus.The purpose of the study is to find the correlation between the speed of breastfeeding and the decrease of pain occurrence on the mother and also give and attention the fourth stage of the labor.The method used in the study is an analytical observation (longitudinal prospective). While the population of study is some mothers who experience a vaginal birth inDahlia I Room at RSU USD Gambiran Kediri.The number of the sample is 29 mothers using a random sampling technique. The independent variable is the speed of first breast feeding and the dependent variable is the decrease of pain occurrence on the fourth stage. The datum are analyzed by ( SPSS ) T analyzed on two random sample and match to the meaningful degree of α< 0,05.The result of the study shows that there is a correlation between the speed of first breastfeeding with the decrease of pain occurrence on the mother .Therefore the conclusion of the study is that there is a correlation between the speed of the first breastfeeding and the decrease of pain occurrence of the mother , so that the researcher hope that the person on duty for the delivery process to encourage the first breastfeeding procedure to the mother and also to enlarge the knowledge of health education of the expecting mother about the essential effect of first breast feeding application.